Proceedings of a Meeting on the harmonization of pesticide legislation and the registration process in the Caribbean - Ministry of Agriculture, Lands and Food Production (Trinidad y Tobago) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
296 páginas. Series Miscellaneous Publication no. 379.